The first integral method for the (3+1)-dimensional modified Korteweg-de Vries-Zakharov-Kuznetsov and Hirota equations - Baleanu, D.; Killi?, B.; Uğurlu, Y.; In?, M. (Editura Academiei Romane, 2015)
The first integral method is applied to get the different types of solutions of the (3+1)-dimensional modified Korteweg-de Vries-Zakharov-Kuznetsov and Hirota equations. We obtain envelope, bell shaped, trigonometric, and kink soliton solutions of these nonlinear evolution equations. The applied method is an effective one to obtain different types of solutions of nonlinear partial differential equations. © 2015 Rom. Journ. Phys.
Keywords: Analytical solutions; First integral method; Hirota equation; Modified Korteweg-de Vries equation; Zakharov-Kuznetsov equation